2016
DOI: 10.3390/su8020171
|View full text |Cite
|
Sign up to set email alerts
|

Regional Competition, Heterogeneous Factors and Pollution Intensity in China: A Spatial Econometric Analysis

Abstract: Regional competition may play an important role in the balance of environmental protection and economic growth. However, it is a pending issue of whether the competition among Chinese local governments leads to a race to black development or green development. This paper aims to explore the strategic interactions in provincial development in terms of an environment-economic indicator, i.e., the pollution intensity in China from 2000 to 2013. We divide four predominant industrial pollutants into two groups acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…Using the spatial lag term by employing the regional Durbin model, the strategic interactions among regions is tested. How pollution intensity is influenced by the direct and spatial spillover effects of environmental regulation was also explored [6]. One paper uses a logit model to examine purchasing propensities [19], another takes the establishment of Poyang Lake Eco-Economic Zone in 2009 as a quasi-natural experiment because of its exogeneity and utilizes the DID method to evaluate its influence on agricultural labor productivity [17].…”
Section: Methodologies Of Energy Economics and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the spatial lag term by employing the regional Durbin model, the strategic interactions among regions is tested. How pollution intensity is influenced by the direct and spatial spillover effects of environmental regulation was also explored [6]. One paper uses a logit model to examine purchasing propensities [19], another takes the establishment of Poyang Lake Eco-Economic Zone in 2009 as a quasi-natural experiment because of its exogeneity and utilizes the DID method to evaluate its influence on agricultural labor productivity [17].…”
Section: Methodologies Of Energy Economics and Managementmentioning
confidence: 99%
“…However, competition among provinces may lead to serious pollution problems and high environmental costs because provincial officials are evaluated based on economic performance. This causes local governments to compete with each other to ease environmental regulation in order to attract investment for economic growth [6]. Thus, whether competition among local governments leads to a race to the bottom, or green development, remains uncertain.…”
Section: Important Issues For China's Energy Economics and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al [26] found that mayors have reduced the total amount of pollution emissions under pressure from the central government and the public during this period. Huang and Xia [27] proved that regional competition affected the intensity of environmental protection from 2002 to 2010 and that environmental regulation is the most effective measure in achieving pollution reduction. Binding targets may also cause strategic behavior in pollution reduction because only a few goals are examined.…”
Section: Total Amount Control Of Water Pollutantsmentioning
confidence: 99%
“…The SEPM is used most often to address the spatial autocorrelation of error items [39]. The SDPM is most useful when the DV should be explained by the IVs in both the region and in other geographical units [40].…”
Section: Spatial Panel Data Modelsmentioning
confidence: 99%